Palladium-Mediated Hydroamination of DNA-Conjugated Aryl Alkenes - Cai, Kunliang; Ran, Yuzhao; Sun, Wenbo; Gao, Sen; Li, Jin; Wan, Jinqiao; Liu, Guansai (Frontiers in Chemistry, 2022)
C-N bond formation is one of the most commonly used reactions in medicinal chemistry. Herein we report an efficient Pd-promoted hydroamination reaction between DNA-conjugated aryl alkenes and a wide scope of aliphatic amines. The described reactions are demonstrated in good to excellent conversions to furnish C(sp3)-N bonds on DNA. This DNA-compatible transformation has strong potentials for the application into DNA-encoded library synthesis.